Sulfate-induced stomata closure requires the canonical ABA signal transduction machinery - Rajab, Hala; Hell, Rüdiger; Wirtz, Markus (Plants, 2019)
Phytohormone abscisic acid (ABA) is the canonical trigger for stomatal closure upon abiotic stresses like drought. Soil-drying is known to facilitate root-to-shoot transport of sulfate. Remarkably, sulfate and sulfide—a downstream product of sulfate assimilation—have been independently shown to promote stomatal closure. For induction of stomatal closure, sulfate must be incorporated into cysteine, which triggers ABA biosynthesis by transcriptional activation of NCED3. Here, we apply reverse genetics to unravel if the canonical ABA signal transduction machinery is required for sulfate-induced stomata closure, and if cysteine biosynthesis is also mandatory for the induction of stomatal closure by the gasotransmitter sulfide. We provide genetic evidence for the importance of reactive oxygen species (ROS) production by the plasma membrane-localized NADPH oxidases, RBOHD, and RBOHF, during the sulfate-induced stomatal closure. In agreement with the established role of ROS as the second messenger of ABA-signaling, the SnRK2-type kinase OST1 and the protein phosphatase ABI1 are essential for sulfate-induced stomata closure. Finally, we show that sulfide fails to close stomata in a cysteine-biosynthesis depleted mutant. Our data support the hypothesis that the two mobile signals, sulfate and sulfide, induce stomatal closure by stimulating cysteine synthesis to trigger ABA production.